2022
DOI: 10.1088/1755-1315/1024/1/012076
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Extraction Yield, and Properties of Biogenic Silica Nanoparticles from Indonesian Rice Husk as Influenced by Solvent Type and Aging Time

Abstract: Rice husk is a rich source of biogenic silica nanoparticles (SNPs) having excellent physico-chemical properties and numerous potential applications. Extraction yield of the biogenic SNPs may be influenced by many factors. In this study, morphology and the influence of solvent type (sodium hydroxide/NaOH, potassium hydroxide/KOH) and aging time (0, 6, 12, 18, 24h) on extraction yield and properties of selected biogenic SNPs from Indonesian rice husk were investigated. The biogenic SNPs were produced by a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Rice husks were collected from a rice milling plant in Karawang District. Analytical grade NaOH and HCl for production of nanobiosilica [2] were purchased from PT Merck Chemicals and Life Sciences. Rice seeds (Oryza sativa) cv.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Rice husks were collected from a rice milling plant in Karawang District. Analytical grade NaOH and HCl for production of nanobiosilica [2] were purchased from PT Merck Chemicals and Life Sciences. Rice seeds (Oryza sativa) cv.…”
Section: Methodsmentioning
confidence: 99%
“…Rice husk contains 15-20% silicon dioxide (SiO 2 ) or silica [3], a beneficial element used widely for various applications, including sustainable rice production [4]. Our study showed that appropriate extraction of rice husk ash could produce biogenic silica nanoparticles powder, which is called nanobiosilica, with individual particle sizes of 20-50 nm [2]. SiO 2 is a chemically bonded compound of silicon (Si) commonly found in nature.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations